2019
DOI: 10.1002/phar.2228
|View full text |Cite
|
Sign up to set email alerts
|

Periprocedural Neuroendovascular Antiplatelet Strategies for Thrombosis Prevention in Clopidogrel‐Hyporesponsive Patients

Abstract: Patients undergoing neuroendovascular procedures such as cerebral aneurysm coiling and intracranial stent deployment are frequently treated with antiplatelet agents to prevent thrombotic complications. The combination of aspirin and a P2Y12 inhibitor such as clopidogrel is often initiated days before elective procedures or as loading doses for emergent procedures; however, some patients may still experience thrombotic complications. Patients identified as clopidogrel hyporesponders are more likely to experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
(120 reference statements)
0
10
0
2
Order By: Relevance
“…Although widely used in the clinic among the numerous platelet activation inhibitors, clopidogrel and aspirin usually have significant gastrointestinal side effects and bleeding risk (Eikelboom et al 2012). Therefore, we utilized cilostazol, because of its low risk of gastrointestinal bleeding, stable effect on platelet inhibition (Barra et al 2019), and increased survival in endotoxemic mice (Chang 2015). After cilostazol application, we observed that the expression of ZO-1 and occludin was increased significantly, the integrity of tight junctions was restored, and intestinal barrier permeability was decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although widely used in the clinic among the numerous platelet activation inhibitors, clopidogrel and aspirin usually have significant gastrointestinal side effects and bleeding risk (Eikelboom et al 2012). Therefore, we utilized cilostazol, because of its low risk of gastrointestinal bleeding, stable effect on platelet inhibition (Barra et al 2019), and increased survival in endotoxemic mice (Chang 2015). After cilostazol application, we observed that the expression of ZO-1 and occludin was increased significantly, the integrity of tight junctions was restored, and intestinal barrier permeability was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this evidence, antiplatelet drugs are promising agents to improve the prognosis of sepsis patients (Wang et al 2018). To study the effect of antiplatelet drug treatment on the intestinal barrier function of septic mice, we applied cilostazol because of its stable effect on platelet inhibition and lower frequency of gastrointestinal bleeding (Barra et al 2019). The mice were divided into four groups, sham + CMC group, sham + Cilostazol group, CLP + CMC group, and CLP + Cilostazol group.…”
Section: Inhibition Of Platelet Activation Improved Intestinal Barrie...mentioning
confidence: 99%
“…Routine monitoring of platelet function in all ischemic stroke patients is not recommended, but it is necessary for patients with recurrent ischemic events. 75,76 Increasing evidence showed that the responses to antiplatelet agents are heterogeneous from non-responders to hyper-responders. 77,78 The phenomenon called antiplatelet resistance is associated with the recurrence of ischemic stroke.…”
Section: The Application Of Teg In Aismentioning
confidence: 99%
“…One group highlighted optimal pharmacotherapeutic strategies for prevention of adverse events in patients receiving extracorporeal life support. Similarly, other reports discuss the application of newer anticonvulsants in the treatment of status epilepticus and neurovascular antiplatelet therapies in complex patients, respectively. Another aspect influencing patient outcomes is their physiologic status.…”
mentioning
confidence: 99%